Nursing theories in the conceptual expansion of good practices in nursing - Marcos Antônio Gomes Brandão; Alba Lucia Bottura Leite de Barros; Cândida Caniçali Primo; Gisele Saraiva Bispo; Rafael Oliveira Pitta Lopes (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To discuss the contribution of nursing theories in the conceptual expansion of good practices in the area for the construction of the unified health system (Sistema Único de Saúde - SUS). Method: Theoretical production of reflection, based on the neomodern framework of philosophy of science. Results: The knowledge and political, social and epistemological commitments of nursing are discussed, highlighting the relationship of the theories with good practices for the construction and application of knowledge in the area in the context of the Brazilian health care system. Reflection on how middle-range theories can help in solving dichotomies between discipline, theory, practice, producers and consumers of knowledge is made. Conclusion: Original reflections on the contributions of disciplinary and professional knowledge of nursing theories to the creation of SUS are presented, defending a creation through the academy-service partnership, in which the theories start being incorporated into a new concept of nursing practices aligned to neomodern principles of science.